Relationship Between Junk Food Consumption Behavior and Calcium Intake with the Incidence of Dysmenorrhea Among Female Students at Poltekkes Kemenkes Riau 2025 - Ambarita, Anna Tirawani; Anggraini, Natashia Yulia (JURNAL KESMAS DAN GIZI (JKG), 2025)
Dysmenorrheaiis a frequent menstrual discomfort among adolescent girls that may greatly disrupt both school performance and everyday activities. Eating patterns, especially junk food consumption and calcium intake, may play a role in the occurrence of dysmenorrhea. This research sought to examine the association between these dietary factors and the incidence of dysmenorrhea among first-year nutrition students at Poltekkes Kemenkes Riau. A quantitative, cross-sectional_design was_employed involving_54 respondents selected through total sampling. Data were collected using a Food Frequency Questionnaire (FFQ), Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and a menstrual pain scale questionnaire. The results revealed that the majority of respondents frequently consumed junk food (57.4%) and had inadequate calcium intake (53.5%). Chi-square analysis showed a significant association between_junk_food consumption (p = 0.037) and calcium intake (p = 0.037) with the incidence of dysmenorrhea. The findings suggest that high junk food consumption and low calcium intake may increase the risk of dysmenorrhea. Therefore, nutrition education promoting healthy eating habits is essential to prevent menstrual disorders among young women.